PENGEMBANGAN SUMBER DAYA MANUSIA BERBASIS KOMPETENSI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA PALU - Andi Asri Cahyani; Syahruddin Hattab; Intam Kurnia (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Indonesian society has entered the era of globalization and modernization in which all aspects have progressed, especially in the fields of technology and information. All challenges must be faced by the people of Indonesia, especially demanding people to become qualified human beings with all the abilities and competencies they have. In connection with these advances, the Personnel and Human Resources Development Agency of Palu City must be able to utilize and manage human resources optimally to keep in line with existing progress and development. This research was analyzed descriptively qualitative. The informants in this study are the Head of the Agency, 1 Head of Division, 2 Heads of Sub Division and 3 staff. The number of informants in the study was 7 people who were drawn by purposive sampling technique. Data collection and retrieval techniques consist of observation, interviews, documentation and triangulation. The theory used in looking at human resource development is the theory put forward by Armstrong.The results showed that competency-based human resource development looks quite good, it can be seen from four aspects, namely Learning, Training, Development and Education. First, the Human Resources development strategy through the Learning aspect is not going well, due to the lack of facilities and infrastructure. Second, in the Training aspect, employees are able to improve employee abilities and performance, improve employee skills and knowledge even though they are unable to significantly change employee attitudes and behavior at work. in the Development aspect, it can be seen that the mentoring and coaching activities obtained by employees in order to develop human resources are effective in providing guidance, support and opportunities for growth for employees. Finally, in the Education aspect, it can be seen that human resource development is able to improve employee performance even though not all education taken by employees can lead to organizational goals.